2014
DOI: 10.1038/srep06465
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant human proinsulin in the milk of transgenic mice

Abstract: There is a steady increasing demand for insulin worldwide. Current insulin manufacturing capacities can barely meet this increasing demand. The purpose of this study was to test the feasibility of producing human proinsulin in the milk of transgenic animals. Four lines of transgenic mice harboring a human insulin cDNA with expression driven by the goat β-casein gene promoter were generated. The expression level of human proinsulin in milk was as high as 8.1 g/L. The expression of the transgene was only detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…In current study, seven F0 female transgenic mice were generated and detected hTPO expression level in the milk by ELISA and Western blot without detecting copy number. Accumulating evidence demonstrated that no direct association was observed between the copy number and the amount of recombinant proteins produced by transgenic mice 36 37 38 39 . Burkov et al ., showed that despite equal copy numbers of the transgene in offspring of #9 and #11 founders, secretion of hGM-CSF in these animals differed.…”
Section: Discussionmentioning
confidence: 99%
“…In current study, seven F0 female transgenic mice were generated and detected hTPO expression level in the milk by ELISA and Western blot without detecting copy number. Accumulating evidence demonstrated that no direct association was observed between the copy number and the amount of recombinant proteins produced by transgenic mice 36 37 38 39 . Burkov et al ., showed that despite equal copy numbers of the transgene in offspring of #9 and #11 founders, secretion of hGM-CSF in these animals differed.…”
Section: Discussionmentioning
confidence: 99%
“…The transgene copy number indicates the number of genomic transgene copies ( 17 ). In a multi-transgenic organism, prior to breeding, it is important to determine the levels of integration and their associations in terms of whether the different copies of integrated genes are consistent ( 18 ). An accurate measurement of exogenous gene copy number is important for establishing a transgenic animal model, in addition to being a prerequisite for follow-up phenotype and gene function analyses ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, E. coli and Saccharomyces cerevisiae are the most common hosts for the production of human insulin (Thim et al 1986;Nilsson et al 1996;Gellissen and Hollenberg 1997;Kjeldsen 2000;Porro et al 2005;Huang et al 2012;Ferrer-Miralles and Villaverde 2013;Baeshen et al 2014). The large-scale manufacture of therapeutic insulin for humans has benefited tremendously from genetic engineering (Arakawa et al 1998;Walsh 2005;Nykiforuk et al 2006;FerrerMiralles et al 2009;Boyhan and Daniell 2011;Qian et al 2011). From 2004 to 2013, biopharmaceuticals were largely derived from E. Coli (24%), yeast (13%), mammalian cells (56%), transgenic animals and plant expression systems (3%) and insect cells (4%) (Gurramkonda et al 2010;Qian et al 2011;Walsh 2012;Nielsen 2013;Walsh 2013;Baeshen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale manufacture of therapeutic insulin for humans has benefited tremendously from genetic engineering (Arakawa et al 1998;Walsh 2005;Nykiforuk et al 2006;FerrerMiralles et al 2009;Boyhan and Daniell 2011;Qian et al 2011). From 2004 to 2013, biopharmaceuticals were largely derived from E. Coli (24%), yeast (13%), mammalian cells (56%), transgenic animals and plant expression systems (3%) and insect cells (4%) (Gurramkonda et al 2010;Qian et al 2011;Walsh 2012;Nielsen 2013;Walsh 2013;Baeshen et al 2014). Transgenic plant expression systems have attracted attention due to advantages such as high-capacity production, safety, inexpensive investment, and fast and easy scale-up (Arakawa et al 1998;Ruhlman et al 2007;Xie et al 2008;Boothe et al 2010;Boyhan and Daniell 2011;Soltanmohammadi et al 2014).…”
Section: Introductionmentioning
confidence: 99%